A self-emulsifying catalytic system for the aqueous biphasic hydroformylation of triglycerides. Issue 9 (9th December 2015) - Vanbésien, T.; Sayede, A.; Monflier, E.; Hapiot, F.
Abstract : The Rh-catalyzed hydroformylation of the CC double bonds of triglycerides (T ) was performed in aqueous medium through the formation of supramolecular complexes resulting from the inclusion of the alkenyl chains ofT into the cavity of modified cyclodextrins (CDs). Abstract : The Rh-catalyzed hydroformylation of the CC double bonds of triglycerides (T ) was performed in aqueous medium through the formation of supramolecular complexes resulting from the inclusion of the alkenyl chains ofT into the cavity of modified cyclodextrins (CDs). MixingT and the aqueous catalytic phase in the presence of CDs led to emulsions that were characterized by phase diagrams and nephelometric measurements. Variations of the nature of the CDs, the reaction temperature, the CO/H2 pressure and the nature of the catalyst allowed for the optimization of the catalytic conditions. The concept was efficiently applied to commercial oils. Molecular dynamics simulations corroborated the experimental data.